Guidelines on the use of liver biopsy in clinical practice from the British Society of Gastroenterology, the Royal College of Radiologists and the Royal College of Pathology. Issue 8 (28th May 2020) - Neuberger, James; Patel, Jai; Caldwell, Helen; Davies, Susan; Hebditch, Vanessa; Hollywood, Coral; Hubscher, Stefan; Karkhanis, Salil; Lester, Will; Roslund, Nicholas; West, Rebecca; Wyatt, Judith I; et al.
Abstract : Liver biopsy is required when clinically important information about the diagnosis, prognosis or management of a patient cannot be obtained by safer means, or for research purposes. There are several approaches to liver biopsy but predominantly percutaneous or transvenous approaches are used. A wide choice of needles is available and the approach and type of needle used will depend on the clinical state of the patient and local expertise but, for non-lesional biopsies, a 16-gauge needle is recommended. Many patients with liver disease will have abnormal laboratory coagulation tests or receive anticoagulation or antiplatelet medication. A greater understanding of the changes in haemostasis in liver disease allows for a more rational, evidence-based approach to peri-biopsy management. Overall, liver biopsy is safe but there is a small morbidity and a very small mortality so patients must be fully counselled. The specimen must be of sufficient size for histopathological interpretation. Communication with the histopathologist, with access to relevant clinical information and the results of other investigations, is essential for the generation of a clinically useful report.